Refractory paroxysmal supraventricular tachycardia in a neonate with WPW syndrome: A case report - B Raj, Aparna; Radhika, S; Kumar S, Sobha; KN, Harikrishnan (Indian Journal of Child Health, 2024)
Supraventricular tachycardia (SVT) is the most common tachyarrhythmia requiring emergency cardiac care in newborns. Neonatal paroxysmal SVT sustained by an atrioventricular node or accessory pathway reentry mechanism, if refractory can lead to congestive cardiac failure, cardiogenic shock, NEC, and death. We report the case of a 14-day-old male full-term neonate diagnosed with Wolff-Parkinson-White syndrome after evaluation for refractory SVT. This case report emphasizes the importance of evaluating cases of neonatal SVT that require multiple doses of adenosine for reversal, with serial electrocardiography and electrocardiographic studies to identify the underlying cause.